2017
DOI: 10.36487/acg_rep/1704_36_basarir
|View full text |Cite
|
Sign up to set email alerts
|

The use of soft computing methods for the prediction of rock properties based on measurement while drilling data

Abstract: Due to recent technological advancements drilling operations conducted for different purposes such as exploration, blasting and even grouting are not considered as auxiliary operations any longer. On the contrary, nowadays onsite drilling operations are considered as important resources for getting more information about rock properties. Many researchers have been working on measurement while drilling (MWD) techniques and their possible use for the prediction of rock mass properties. This paper presents a lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Parameters such as sound intensity level (dB) or vibration level (Nm/s) were also used to recognize rock mass features [13,14,[20][21][22][23][24][25], as well as the possibility of predicting the percentage of iron ore in the rock, based on the penetration rate and torque. Kahraman et al attempted to correlate rock properties with drilling progress [26], and showed the relationship between drilling penetration rate and rock resistance to uniaxial compression.…”
Section: Technological Methods Based On the Borehole Drilling Processmentioning
confidence: 99%
“…Parameters such as sound intensity level (dB) or vibration level (Nm/s) were also used to recognize rock mass features [13,14,[20][21][22][23][24][25], as well as the possibility of predicting the percentage of iron ore in the rock, based on the penetration rate and torque. Kahraman et al attempted to correlate rock properties with drilling progress [26], and showed the relationship between drilling penetration rate and rock resistance to uniaxial compression.…”
Section: Technological Methods Based On the Borehole Drilling Processmentioning
confidence: 99%
“…In theory, various methods, including analytical, numerical, and experimental, can be used to analyze the applicability of MWD to the characterization of coalmine roofs [2][3][4][5][6][7][8]11,[15][16][17]. Analytical and numerical methods provide a straightforward means to understand the immediate effect of various geotechnical parameters on drilling and bolting operations.…”
Section: Methodsmentioning
confidence: 99%
“…The method was first developed for the petroleum exploration industry [2]. The literature has examples of laboratory experiments, field trials, and the development of instruments to monitor while drilling [2][3][4][5][6][7][8][9][10][11][12]. Reference [6] provided a brief review of recent improvements on instrumented drills used in ground characterization and highlighted issues that are still lagging in using these instruments.…”
Section: Mwd Historymentioning
confidence: 99%
“…From the data analysis, it could observe that the corresponding PR for the applied thrust was most impacting the UCS, followed by thrust. The prediction of rock strength and geological conditions around and in the blasting area could be possible using measurement while drilling (MWD) data [5,15,21]. Using the various bits at a different angle of attack, an attempt was made to determine the cuttability of rocks [22].…”
Section: Literature Reviewmentioning
confidence: 99%